2010
DOI: 10.1111/j.1601-0825.2010.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and periodontal diseases: an overview of the post‐HAART era

Abstract: Oral Diseases (2010) 17, 13–25 HIV infection remains a global health problem of unprecedented dimensions, although the development of highly active antiretroviral therapy (HAART) has significantly modified the course of HIV disease into a manageable chronic disease with longer survival and improved quality of life in HIV‐infected subjects. Among the HIV‐associated infections, oral lesions have been recognized as prominent features since the beginning of the epidemic and continue to be important. Periodontal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 111 publications
(139 reference statements)
2
89
0
8
Order By: Relevance
“…Higher prevalence of periodontal disease has been observed in HIV patients (4,5). The symptoms of periodontal disease in HIV patients are very distinctive and more severe (6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Higher prevalence of periodontal disease has been observed in HIV patients (4,5). The symptoms of periodontal disease in HIV patients are very distinctive and more severe (6).…”
Section: Discussionmentioning
confidence: 94%
“…However, it remains unclear why oral KS occurs only in a subset of patients. Clinically, it has been noticed that HIV patients display a higher prevalence of periodontal disease with more severe symptoms (4)(5)(6). Accumulating evidence supports the notion that periodontal disease creates an oral microenvironment that stimulates KSHV replication and infection, contributing to oral KS development.…”
mentioning
confidence: 99%
“…characterized by a significant increase in generalized immune activation (1,2) and in mucosal inflammatory conditions such as periodontitis and gingivitis (3)(4)(5)(6). Some studies have reported an increased migration of inflammatory cells into the oral mucosa (7), whereas others have shown that levels of proinflammatory cytokines such as interleukin-6 (IL-6) (8-10) were significantly elevated during HIV infection.…”
Section: Hronic Human Immunodeficiency Virus (Hiv) Infection Ismentioning
confidence: 99%
“…Oral candidiasis is a particularly common problem in HIV-infected individuals, although the introduction of HAART has led to a decline in its incidence (Hodgson et al, 2006). Infection with HIV is also associated with the periodontal diseases: linear gingival erythema, nectrotizing ulcerative gingivitis (NUG) and acute necrotizing periodontitis (ANP) (Mataftsi et al, 2011). NUG and ANP typically have a sudden onset and can cause severe pain.…”
Section: Introductionmentioning
confidence: 99%